Diurnal Variation of Essential Oil Ratio and Composition Of Some Basil Genotypes - Aygun, Yusuf Ziya; Eren, Yilmaz; Ertekin, Esra Nermin (Bangladesh Journal of Botany, 2022)
The change of essential oil ratios and components of five different basil genotypes harvested at different times (00:00, 06:00, 12:00, 18:00) in day was investigated. Plants were grown under the field conditions and essential oils of the plants were extracted by hydro-distillation method. Identification of essential oil components were performed by GC-MS. It was the G5 genotype that had the highest essential oil content in all plant parts, regardless of the time of day. The highest essential oil content (2.8%) was obtained from the dry leaves of the G5 genotype from the sampling made at 18:00. The main components of essential oils were determined as linalool, eucalyptol, trans α-bergamotene, methyl cinnamate, α-muurolol and eugenol. However, while the ratios of these components differed between genotypes, the changes in time of day were similar for some components. Linalool content tended to increase mostly in the middle of the day. This study indicated that essential oil ratio and components of different basil genotypes significantly differed according to harvesting times in day. Bangladesh J. Bot. 51(4): 787-795, 2022 (December)